2008
DOI: 10.1007/s00426-008-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Control by action representation and input selection (CARIS): a theoretical framework for task switching

Abstract: Control by action representation and input selection (CARIS) is a modeling framework for task-switching experiments, which considers action-related effects as critical constraints. It assumes that control operates by choosing control parameter values, representing input selection and action representation. Competing CARIS models differ in whether (a) control parameters are determined by current instructions or represent a perseveration, (b) current instructions apply to the input selection and/or to action rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 90 publications
7
123
1
Order By: Relevance
“…It seems likely that the size judgment task includes at least two levels of decision: task decision and response selection. Task decision is widely assumed to precede response selection in task-switching studies (see, e.g., Meiran, Kessler, & Adi-Japha, 2008;Monsell, 2003;Rubinstein, Meyer, & Evans, 2001), and a recent study showed that the task-decision process was differentiated from the response-selection process (Braverman & Meiran, 2010). As was described above, we assume that the phonological loop may support resolving conflict during the task-decision process, not during the response-selection process.…”
Section: Congruity Effects and Articulatory Suppressionmentioning
confidence: 97%
“…It seems likely that the size judgment task includes at least two levels of decision: task decision and response selection. Task decision is widely assumed to precede response selection in task-switching studies (see, e.g., Meiran, Kessler, & Adi-Japha, 2008;Monsell, 2003;Rubinstein, Meyer, & Evans, 2001), and a recent study showed that the task-decision process was differentiated from the response-selection process (Braverman & Meiran, 2010). As was described above, we assume that the phonological loop may support resolving conflict during the task-decision process, not during the response-selection process.…”
Section: Congruity Effects and Articulatory Suppressionmentioning
confidence: 97%
“…Mayr and Keele (2000), for example, suggested that "task sets are assumed to specify the configuration of perceptual, attentional, mnemonic, and motor processes critical for a particular task goal" (p. 5), thereby highlighting the relevance of cognitive parameter settings in situations with ambiguous stimulus input, but where a specific goal is to be reached. Such processing-related conceptualizations of task sets are typical for formal models of task switching (e.g., in the parallel distributed processing-model [PDP-model] by Gilbert & Shallice, 2002; in executive control of the theory visual attention [i.e., ECTVA], Logan & Gordon, 2001; in control by action representation and input selection [i.e., CARIS], Meiran et al, 2008).…”
Section: Task Switching and The Conceptualization Of Task Setsmentioning
confidence: 99%
“…In Meiran's (2000) model the resetting of perceptual selection parameters required by a task-switch can be done early, in advance of the stimulus (the preparation interval permitting), whereas S-R biases can only be reset following response selection -hence the 'residual' switch cost. But in the more recent CARIS framework (Meiran et al, 2008), the model reported to fit the empirical data best contained no advance (pre-stimulus) resetting of perceptual selection parameters on switch trials, though response selection parameters could be reset in advance; the authors suggested that when the task changes the stimulus may need to be physically present for perceptual (attentional) reconfiguring to take place.…”
Section: Spatial Attention In Task-switchingmentioning
confidence: 99%